Implementasi Kontroler PI Pada Buck Converter Sebagai Pengaturan Tegangan Konstan Di Sistem Turbin Angin Permanent Magnet Schronous Generator (PMSG) Dilengkapi Sistem Monitoring Berbasis IoT - muhammad zainal arifin; Ratna Ika Putri (Indonesian Society of Applied Science (ISAS), 2021)
The need for electrical energy has become a primary need for humans, until now the energy used to generate electrical energy is fossil fuels whose numbers are dwindling. Renewal of energy is needed through renewable energy, namely using unlimited wind energy. The wind speed is always changing in a fluctuating manner which can affect the output voltage at the power plant. In this study, the wind turbine used is a permanent magnet synchronous generator, the output voltage from the generator is a 3-phase electric voltage which is then rectified into a DC voltage. To be able to stabilize the voltage, a buck converter circuit is used as a voltage reducer, the switching control used in the buck converter uses a half bridge with IC IR2110 with a frequency of 31.5 kHz. The buck converter can reduce the voltage with an input voltage range of 30-100 Volts with a duty cycle of 10- 90%, the PI control system on the buck converter circuit for constant voltage regulation of 27 Volts (settpoint) and using the IoT thingspeak website for remote monitoring.